Pedagogicheskie aspekty podgotovki zhenshchin, zanimayushchikhsya sportivnoi bor'boi - Tarakanov, B. I. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this paper was to consider the main pedagogical aspects of women's sport training in wrestling events. The author represents the materials of women's sport wrestling development and the retrospective analysis of the scientific researches in that area. He offers the main directions to elaborate the system of pedagogical aspects in women's sports wrestling training.